Mudando a cena no ensino de ciências: contribuições do teatro problematizador - Felippe, Mariana Gonçalves (2017)
This research analyses which perspective of theatre can be utilised as a method of teaching Science, serving as a dynamic for the construction of scientific knowledge through playful activities. That said, theatrical workshops were developed, at “Escola Estadual Julio Bierrenbach”, in the city of Sorocaba, utilising Paulo Freire and his moments proposed in the piece “Pedagogia do Oprimido” as well as chapter three and Augusto Boal and the Theatre of the Oppressed, as inspiration. The activities that were developed at the public school were analised through two categories chosen to find out the limites and overcomings of the students with the educational practices which are problematisation and dialogue. The research characterises itself as qualitative, in that the voice of the participants is fundamental to the analysis and development of the practice. In this way, we seek to make a critical analysis of the current scientific teachings in this text, with the basis of authors who discuss the theme as well as investigate the theatre in school education and the Science of nature, its limits and possibilities in the curricular practice. The developed practice, as the results show, had limites and advances which allows us to conclude that working on the problematisation of theatre in critical and dialogic perspective shows itself as fundamental to the development of independence and emancipation of individuals, where students show, during the practice, principles of a new outlook towards reality.